Transient Localized Rotating Structures in a Suspension of Highly Thermophilic Nanoparticles - Carpineti, Marina; Castellini, Stefano; Pogliani, Andrea; Vailati, Alberto (Frontiers in Physics, 2022)
A thermophilic suspension of nanoparticles heated from below exhibits a complex stability diagram determined by the competition between the stabilizing flux of nanoparticles induced by thermophoresis and the destabilizing flux determined by thermal convection. We investigate Rayleigh-Bénard convection in a suspension of highly thermophilic nanoparticles with large negative separation ratio ψ = −3.5 heated from below. We show that transient localized states appear in the range of Rayleigh numbers 2200<Ra<3000. These states rotate rapidly around their axis and gradually shrink in size until the system returns in a purely conductive state. We discuss how these states are originated by the travelling waves arising from the competition between Rayleigh-Bénard convection and the solutal stabilisation of the sample.